2018
DOI: 10.1002/jlb.2mir0817-342r
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of type I IFN signaling

Abstract: Type I IFNs (α, β, and others) are a family of cytokines that are produced in physiological conditions as well as in response to the activation of pattern recognition receptors. They are critically important in controlling the host innate and adaptive immune response to viral and some bacterial infections, cancer, and other inflammatory stimuli. However, dysregulation of type I IFN production or response can contribute to immune pathologies termed "interferonopathies", pointing to the importance of balanced ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 196 publications
(205 reference statements)
5
86
0
Order By: Relevance
“…[6, 12, 22, 33] Type I IFN activation can either induce inflammation following a viral or bacterial infection, or contain a suppressive role in certain chronic infections [1, 11]. Variability in this response is highly dependent on cell type, pathogens and the environmental context [1]. In rats, we showed that post-MI IFN-α administration altered the distribution of circulating monocyte subsets towards the pro-inflammatory CD43-lo monocyte at day 2 in comparison to placebo, a shift which has generally been associated with an expanded infarcted area [31, 32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6, 12, 22, 33] Type I IFN activation can either induce inflammation following a viral or bacterial infection, or contain a suppressive role in certain chronic infections [1, 11]. Variability in this response is highly dependent on cell type, pathogens and the environmental context [1]. In rats, we showed that post-MI IFN-α administration altered the distribution of circulating monocyte subsets towards the pro-inflammatory CD43-lo monocyte at day 2 in comparison to placebo, a shift which has generally been associated with an expanded infarcted area [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Type I IFN activation occurs classically through the IFN-α receptor (IFNAR). This induces activation of the Jak–Stat pathway resulting in Stat1 and Stat2 dimerization that initiates nuclear translocation of IFN regulatory transcription factors (IRF) and subsequent transcription of ISGs [1, 7, 23]. King et al demonstrated that MI activates IRF3-dependent signalling through macrophages upon dsDNA sensing at day 4 following MI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As reported, IAV infection can contribute to ALI, 2 which is associated with excessive type I IFN (especially IFN-a) production, 41 and IRF7 is a major transcription factor for the production of IFN-a. 30 We speculated that IRF7 played a key role in local immune responses, and correlated with IAV-induced ALI.…”
Section: The Role Of Irf7 In Local Immune Responses Induced By Iavmentioning
confidence: 90%
“…Despite this, production of type I IFNs is not specific for non-sterile pathologies. In various sterile pathologies, type I IFNs play either a disease ameliorating (e.g., cancer) or even a disease exacerbating role (e.g., autoimmune diseases especially interferonopathies) (Arimoto et al, 2018;Burdick et al, 2009;Durbin et al, 2000;Palucka et al, 2005;Rizzo et al, 2014). This is made possible by a major overlap (in terms of shared cognate PRRs) between danger signals derived from pathogens (together classified under the term, pathogen-associated molecular patterns or PAMPs) and those of "self" or endogenous origin (together classified under the term, damageassociated molecular patterns or DAMPs); as well as the ubiquitous expression of IFNAR1/2 (de Weerd et al, 2013;Garg and Agostinis, 2017;Garg et al, 2017c;Ragimbeau et al, 2003;Rubartelli and Lotze, 2007).…”
Section: Type I Interferons: An Introduction 21 Mechanisms Underlyinmentioning
confidence: 99%